EFFECTS OF PRENATAL YOGA ON THE ANXIETY OF PREGNANT WOMEN BEFORE BIRTH - Setiyarini, Anggraini Dyah; Putri , Ellatyas Rahmawati Tejo; Andini, Dwi Margareta; Rahmawati, Erna (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Anxiety in the last trimester of pregnancy will be different from anxiety in the previous trimester. Stress during pregnancy will affect the growth and development of the fetus. Anxiety is three times more likely to increase fear of childbirth and 1.7 times more likely to require a cesarean section. Stress during pregnancy can be reduced by exercising. One of the recommended sports is prenatal yoga. Practicing prenatal yoga during pregnancy is more effective in reducing stress and depression. Because in yoga, in addition to practicing, pregnant women also receive positive affirmations so that they can respond to physical changes during pregnancy and childbirth. to determine the effect of pregnancy yoga on the anxiety of pregnant women before birth. Method: A study uses a quasi-experimental design to examine the impact and effectiveness of treatment. The design of this study uses groups of subjects. Observations will be made before and after treatment. The sample for this study was pregnant women between 14 and 40 weeks of gestation. The instrument used to measure anxiety levels is the standard Hamilton Anxiety Rating Scale questionnaire (HARS). This research was carried out in the working area of "‹Puskesmas Ngletih, Kediri Regency. The study population included all pregnant women who attended a yoga class for pregnant women at Puskesmas Ngletih Workspace, Kediri Regency, for a total of 12 people. Result: The results of a study conducted at Ngletih Community Health Center, Kediri Town, in 2023. Result : Practicing gentle yoga before giving birth has an effect on pregnant women's anxiety about labor, with a p value of <0.001 (p <0.05).Conclusion : It is hoped that all pregnant women with a gestational age of 14–40 weeks can do prenatal yoga.